Monitoring of Cd and GSH contents and Bn-OASTL expression in transgenic tobacco seedlings in response to Cd stress - Xiaolan He; Jianwei Wang; Wenxu Li; Xinhong Chen (PLoS ONE, 2026)
Cadmium (Cd) pollution threatens agricultural productivity and food safety. O- acetylserine(thiol)lyase ( OASTL ) genes have been tied to plant responses to heavy metal stress, yet their roles in heterologous systems, particularly in Cd accumulation and tolerance, remain unclear. Here, we isolated a novel OASTL gene, BnaOASTL , from the high-Cd-accumulating oilseed rape cultivar Brassica napus “Nanyou 868” and expressed it in tobacco ( Nicotiana benthamiana ). Transgenic lines were exposed to Cd stress, and Cd content, glutathione (GSH) level, and BnaOASTL expression were evaluated. The full-length BnaOASTL cDNA (969 bp) encoded a cytoplasmic/nuclear protein of 322 amino acids. Under Cd stress, Bn-OASTL expression was significantly upregulated in transgenic plants, particularly in roots. However, compared with wild-type, transgenic lines showed no improvement in Cd tolerance or accumulation and no significant changes in GSH levels. The findings suggest that although BnaOASTL is transcriptionally responsive to Cd stress, its overexpression alone does not confer altered Cd tolerance or accumulation in tobacco. The study highlights the complexity of Cd response mechanisms and suggests that BnaOASTL functions within a broader, species-specific regulatory network.